Creating the Opium War British imperial attitudes towards China, 1792-1840 - Gao, Hao (Studies in imperialism, 2020)
Creating the Opium War examines British imperial attitudes towards China during their early encounters from the Macartney embassy to the outbreak of the Opium War - a deeply consequential event which arguably reshaped relations between China and the West in the next century. It makes the first attempt to bring together the political history of Sino-western relations and the cultural studies of British representations of China, as a new way of explaining the origins of the conflict. The book focuses on a crucial period (1792-1840), which scholars such as Kitson and Markley have recently compared in importance to that of American and French Revolutions. By examining a wealth of primary materials, some in more detail than ever before, this study reveals how the idea of war against China was created out of changing British perceptions of the country.